MATCHING GAME TO ENRICH STUDENTS’ VOCABULARY ACHIEVEMENT: (A Study Conducted at SMP Negeri 1 Siau) - joykson haronis; Noldy Pelenkahu; Ignatius J. C. Tuerah (SoCul: International Journal of Research in Social Cultural Issues, 2022)
This study is to prove whether the use of the Matching Game in teaching vocabulary can achieve students’ vocabulary or not. In doing this research, the writers use quantitative research through post-test only with an experimental group and a control group. The experimental class is taught in test after treatment and the control class is taught by conventional method. This study is conducted on students in the second grade of SMPN 2 East Siau. The sample is taken from one class of junior high school. After conducting research, it can be concluded that the use of Matching Games is very effective in improving a student's English vocabulary skills. It also further supports that the selection of appropriate and educational games greatly affects the output of each learner, of course, by taking into account demographic factors and the background of each student in order to increasingly provide games that match their interests.